Peningkatan Infrastruktur Desa dengan Pembuatan Papan Petunjuk Jalan - Sholihah, Nikmatus; Arti, Erni Cahya; Sulistoiyowati, Yuni; Fauziyah, Nur Ida Zuliatin; Cahyo, Rifko Harny Dwi; Rohmah, Annisa Nidaur (TAAWUN, 2023)
A number of roads in several villages have major problems, namely damage to several road points and intersections and the absence of road signs and village maps. This problem also occurs in Sewor Village, Sukorame District, Lamongan, East Java. In order to overcome this and facilitate road access to each hamlet in Sewor Village, the community service team located in Sewor Village plans to procure road signs in each local hamlet to facilitate and complete the infrastructure for directions to the hamlets located in Sewor Village. The activity was carried out in Sewor Village, Sukorame District in 5 hamlets namely Ngrapah Hamlet, Nemon Hamlet, Ngengkreng Hamlet, Kedungdowo Hamlet, and Sewor Hamlet. This community service activity consists of 4 stages of activity, namely first conducting research and field surveys at the location. Second, preparing tools and materials for designing road signs for each hamlet. Third, the process of assembling boards and painting was carried out and the last stage was installing road signs in each hamlet by students assisted by youths and the surrounding community. There are 9 Hamlet road signs and 6 poles. The program received support and assistance from the Sewor Village Government, youth, and the Sewor Village community so that it could be implemented properly. In the process of activities from preparation to implementation of the program, no significant obstacles were found. In addition, based on 3 survey indicators the level of community satisfaction in community service activities regarding the procurement and installation of signboards shows that the community is satisfied with the existence of the program.